Pengembangan pembelajaran blended learning pada generasi Z - Agus Purnomo; Nurul Ratnawati; Nevy Farista Aristin (Jurnal Teori dan Praksis Pembelajaran IPS, 2016)
Every generation has beliefs, values, cultures, perspectives, interests, and different skills for life and work. The generation born in the early 2000s when the rapid development of such technology referred to as generation-z or net generation. Characters of this generation is very sensitive to technology and communication, meaning they have an advantage in the field of information and knowledge development. While the educators who were born in an earlier era are still not familiar with it so that educators often claimed to be "clueless" (stuttering technology). To address this need no new innovations in the learning process so that it complies with these characters. Combines conventional learning with communication media such as whatsapp and google drive is one easy solution social studies lesson on the generation-z. Learners who are accustomed to communicate using social networks can access the material and lesson plans that have been prepared with structured each meeting. So that they can read or prepare questions before the learning begins. The proportion of the use of e-learning in this study reached 35% so that it can be summed up as learning blended learning. This learning to stand on its information technology infrastructure and can be done anytime and anywhere. So learning blended learning has characteristics that are open, flexible, and can occur anywhere.Keywords: Generation Z and blended learning http://dx.doi.org/10.17977/um022v1i12016p070